The Contemplative Vision in the poetry of Ibn Jubeir al-Andalusi - ATTIYA, bushra abd attiya (Journal of College of Education, 2021)
The research deals with the study of the contemplative poetry of Ibn Jubayr. The research began with the definition of meditation as a language and a term with the presentation of examples of contemplative poetry in the Arab poetic heritage. In the first part , I studied the motives of the contemplative poetry, which were represented in the experiences of life, alienation, asceticism and wisdom. In the second chapter, I dealt with the artistic features that emerged in the poetry of meditation and were represented in the artistic construction and poetic image. From the research, we find that the poetry of meditation combines both mental attribute and emotion, and was like the poet’s vision and reflections in life and came in the form of poems or poems arranged within different purposes and distinguish the meditative poetry in clarity and simplicity as well as carrying human and instructive values